Analysis of highly conserved regions of the 3'UTR of MECP2 gene in patients with clinical diagnosis of Rett syndrome and other disorders associated with mental retardation - Santos, Mónica (2008)
In this work we explored the role of the 3'UTR of the MECP2 gene in patients with clinical diagnosis of RTT and mental retardation; focusing on regions of the 3'UTR with almost 100% conservation at the nucleotide level among mouse and human. By mutation scanning (DOVAM-S technique) the MECP2 3'UTR of a total of 66 affected females were studied. Five 3'UTR variants in the MECP2 were found (c.1461+9G>A, c.1461+98insA, c.2595G>A, c.9961C>G and c.9964delC) in our group of patients. None of the variants found is located in putative protein-binding sites nor predicted to have a pathogenic role. Our data suggest that mutations in this region do not account for a large proportion of the RTT cases without a genetic explanation.